COVID-19 and exercise. Resources and support for keeping your patients or clients active during the coronavirus (COVID-19) pandemic (American College of Sports Medicine, 2020)
As we grapple with the consequences of the coronavirus (COVID-19) pandemic, it`s easy to forget an important component of health related to the immune system: exercise!